Klasifikasi Siswa Berprestasi Pada SDN Puncu 3 - Ahmad Fakhruddin Luthfi; Daniel Swanjaya; Resty Wulanningrum (Teknik Komputer Fakultas Teknik Universitas Islam Kadiri (UNISKA), 2022)
In the world of education, the increasing success and failure of students is a reflection of the world of education. Education is currently required to be able to compete with all the utilization of existing natural resources. This study aims to determine which students will be ranked in the top 5 in grade 6 semester 2 every year at SDN Puncu 3. This study uses the method of self organization maps (SOM). The data that has been obtained from the data recap of the student data values ​​uses the SOM method. The SOM method analyzed data from 75 students of SDN Puncu 3 with a silhouette coefficient value of 0.7399. Keywords: Clustering, Education, Self Organizing Map.